How long is now - Soo, Yu Neng (Nanyang Technological University, 2023)
An adventure drama following the reopening of the border in post-pandemic, KY a working adult returns to his hometown in Penang with Ah Lim, a private car hire. Along the way they uncover KY’s personal struggles and Ah Lim brings about an unexpected change in his attitude towards life.